Low molecular weight heparin and survival in cancer (Hematology Meeting Reports, 2009)
More recent clinical trials have evaluated the potential benefits of low molecular weight heparin therapy in prolonging survival in patients with solid tumour malignancy. The Fragmin Advance Malignancy Outcome Study (FAMOUS) randomised 385 patients to receive the low molecular weight heparin dalteparin sodium (5000 units once daily) or normal saline placebo injections for up to 1 year. Patients in this trial had advanced disease (locally advanced or disseminated). The primary endpoint of this study was mortality one year after randomisation. 46% of dalteparin patients compared to 41% of placebo group patients were alive at 1 year (p=n.s). In a post-hoc sub-group analysis of good prognosis patients (n=102) dalteparin administration was associated with an increase of median survival from 24 months in the placebo group to 43 months in the dalteparin group.